Sediment contamination by heavy metals and ecological risk assessment: The case of Gulf of Pozzuoli, Naples, Italy. (June 2020) - Arienzo, Michele; Ferrara, Luciano; Toscanesi, Maria; Giarra, Antonella; Donadio, Carlo; Trifuoggi, Marco
Abstract: Heavy metal concentrations in sediments of the Gulf of Pozzuoli, GoP, and northwest of the Gulf beyond Monte di Procida, MdP, were determined. The enrichment factor, EF, revealed in GoP strong pollution with peaks for Cr and Cu of 61.1 and 96.9. High EF Cr, Cu, and Ni values were observed for MDP. Geoaccumulation index, Igeo, rates GoP extremely polluted by Cr and Cu, Igeo > 5, and MdP heavily polluted by Cr, moderately to heavily polluted by Cu, and heavily to extremely polluted by Ni. Contamination factor, Cf, was high in GoP and varied: Cu > Cr > Ni > Cd > Hg > Zn > Pb > As, and those of Cr, Cu and Ni largely surpassed the thresholds in MdP. The ecological and comprehensive ecological risk placed Cr, Cu, Hg and Ni at high or serious risk level in the Gulf, with a peak of 465 for Cu and at a moderate level in MdP except for a very high risk for Ni. Highlights: EF and Igeo revealed strong accumulation of heavy metals. PCA showed high association of Cd, Cr, Cu, Fe, Hg, Pb, Zn due to metallurgic activity. Ni contamination was related to shipyards of the port of Baia in W-Gulf of Pozzuoli. As contamination links to submarine hydrothermal springs. Pollution and ecological risk spread far beyond the Gulf of Pozzuoli.